Diminished rights : Danish lone mother families in international context - Polakow, Valerie (Policy Press, 2001)
Diminished rights is a unique qualitative study that documents the daily lives of vulnerable lone mothers and their children in Denmark. Loss of rights, gender and ethnic inequality, and family violence all emerge as key themes with far-reaching international implications. Policy and practice recommendations are made with wide-ranging applications for an international audience of policy makers, practitioners and academics.